IMPLEMENTATION OF THE "SCIENCE PATH" VARIANT PROGRAM IN PREPARING CHILDREN FOR SCHOOL - Nazarova Dilnoza Orazaliyevna; Marufova Munira Egamkulovna (Zeta Repository, 2023)
This article is for pedagogues, it describes ways to solve communication problems in pre-school education organizations in preparing 6-7-year-old children for school through the "Science path" variant program.